Neuroschistosomiasis in an eight year old male: A case report - Ikenna Ndu; Ijeoma Obumneme-Anyim; Uchenna Ekwochi; Ogechukwu Amadi (National Scientific Medical Center, 2020)
Background: Schistosomiasis is a helminthic infestation of public health importance. Central nervous system involvement is a severe but under reported complication. Case report: This was a case of neuroschistosomiasis in an eight year old male who lived in a rural community in Enugu, South East Nigeria. Patient had presented with terminal haematuria, headache and neurological complications. Urine microscopy showed many ova of schistosoma haematobium while ultrasound showed urinary bladder base changes that appeared irregular with hyper echoic mucosa and focal mucosal thickening on the right side. Computed tomography of the brain revealed a hyper dense oval area surrounded by an irregular hypo dense area in the left parietal region overlying the left thalamus and lentiform nucleus. Patient showed good clinical response to praziquantel and corticosteroid. Conclusion: Neuroschistosomiasis is a rare complication of schistosomiasis. A high index of suspicion should be entertained in endemic areas as early treatment with praziquantel and steroids has good outcome.